Corynebacterium striatum prosthetic valve endocarditis. A case report and literature review. (October 2020) - Mansour, Mohamed Kamal; Al-Messabi, Ahmed Hussain; Ahmed, Sundos Abdulla; Jabeen, Fouzia; Moumne, Ibrahim Salah; Nsutebu, Emmanuel Fru
Highlights: It is important to recognize Corynebacterium species as a cause of infection when grown from blood culture in immunocompromised patients and patients with prosthetic devices. It is important to consider the diagnosis of infective endocarditis in patients with recurrent bacteremia and an unclear source. A patient with Corynebacterium striatum prosthetic valve endocarditis was successfully treated with four weeks of intravenous benzylpenicillin. However further data is required to determine the optimal duration and treatment regimen. Abstract: Background: Corynebacterium striatum is a Gram-positive bacillus. It is one of the normal commensal flora of the skin and mucous membranes. It is generally considered to be a contaminant when grown in blood culture, however, it is increasingly recognized as a cause of infection in patients with prosthetic devices. Case report: We report a case of a 79-year old female with a prosthetic metallic mitral valve, who presented to our hospital with a four-day history of fever and chills. She was diagnosed with Corynebacterium striatum prosthetic valve endocarditis, in view of positive blood cultures for the microorganism, grown on two occasions, and the presence of a vegetation at the base of the prosthetic mitral valve on transesophageal echocardiography. The patient was treated with a four weeks course of intravenous benzylpenicillin with good outcomes. Conclusion: Corynebacterium striatum is an uncommon cause of prosthetic valve endocarditis. It should not be considered a contaminant, particularly when grown in a blood culture in immunocompromised patients or patients with prosthetic devices. More data is required to determine the optimal duration and treatment regimen for Corynebacterium striatum endocarditis.